2011
DOI: 10.1371/journal.pone.0027353
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Response of Primary Cells Relevant to Dialysis-Related Amyloidosis to β2-Microglobulin Monomer and Fibrils

Abstract: The formation of insoluble amyloid fibrils is associated with an array of devastating human diseases. Dialysis-related amyloidosis (DRA) is a severe complication of hemodialysis that results in the progressive destruction of the bones and joints. Elevated concentrations of β2-microglobulin (β2m) in the serum of subjects on hemodialysis promote the formation of amyloid fibrils in the osteoarticular tissues, but the cellular basis for the destruction of these tissues in DRA is poorly understood. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…Fibril samples were stored at 25°C and used within 3 mo. To prepare fibrils for confocal imaging, β 2 m monomers were labeled with TMR, as described in Porter et al (49) and as detailed in SI Methods. Liposome Preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibril samples were stored at 25°C and used within 3 mo. To prepare fibrils for confocal imaging, β 2 m monomers were labeled with TMR, as described in Porter et al (49) and as detailed in SI Methods. Liposome Preparation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, β 2 m fibrils formed under acidic conditions are structurally similar to those formed in vitro at near-neutral pH from the N-terminally truncated β 2 m variant, ΔN6 (21). They also display similar effects (internalization into the endo-lysosomal pathway and the inhibition of cellular reduction of MTT) when incubated with cell lines and with primary cells relevant to the pathology of dialysisrelated amyloidosis (DRA) (monocytes, chondrocytes, and osteoblasts) (9,10,23,24). Moreover, fibrils formed from ΔN6, but seeded with wild-type β 2 m fibrils formed at low pH, have been shown to inhibit osteoclast formation from primary human monocytes, rationalizing the osteoarticular pathology associated with DRA (23).…”
Section: Significancementioning
confidence: 91%
“…pH values of 7.4 and 6.4 were chosen to mimic the environments encountered by fibrils in the extracellular milieu and in early endosomes, respectively. In previous experiments we have shown that β 2 m fibrils are taken up into endosomes and lysosomes in a lengthdependent manner, wherein they persist as protease-resistant material that retains a cross-β structure and results in the perturbation of lysosome function (10,23,24). pH-induced changes in fibril yield and conformation were monitored by ThT fluorescence and SDS-PAGE (Methods).…”
Section: Significancementioning
confidence: 99%
“…After ten years of dialysis, 80% of patients show stiffness in large joints, 64% show a restriction in movements, and 43% show carpal tunnel syndrome [7,8]. Less frequent is cubital tunnel syndrome [9]. The known main causes of this condition are beta-2 microglobulin deposits in the joints of patients due to insufficient elimination of this protein during therapy [10].…”
mentioning
confidence: 99%